The role of radical right parties in escalating parliamentary conflict: policy issues and party responses in Portugal - Santos, Nelson; Serra-Silva, Sofia; Silva, Tiago (Frontiers in Political Science, 2025)
The rise of radical right parties (RRPs) across democracies has raised pressing questions, particularly as they gain parliamentary representation even in contexts previously considered resistant to their influence. Typically adopting confrontational and polarizing approaches, RRPs challenge not only government policies but also foundational political norms, creating significant uncertainty within legislative bodies. While much of the existing research has focused on their discourse strategies, there remains a limited understanding of how these parties influence parliamentary dynamics after they enter national parliaments. We examine the role of the Portuguese radical right party Chega in reshaping parliamentary dynamics, specifically conflict, following its rapid rise in 2019—a striking development in a country previously considered immune to such phenomena and with a party system known for being highly stable. We approach conflict by examining unanimous and without opposition votes, assessing the frequency with which each party finds itself on the losing side of a vote, and calculating a disagreement index (DI) for each legislative term. Additionally, we measure conflict across various policy areas and identify its sources by distinguishing between conflict driven by Chega’s behavior toward other parties and conflict triggered by other parties’ responses to Chega’s legislative proposals. Our analysis draws on parliamentary votes from 2002 to 2024, encompassing all parties with representation in the Assembleia da República. Our findings reveal that Chega’s entry has significantly accelerated the ongoing erosion of parliamentary consensus, further reinforcing broader transformations within the Portuguese parliament. The study demonstrates how radical right parties serve as powerful drivers of parliamentary conflict, both by introducing highly polarizing issues—primarily related to Civil Rights and Liberties, as well as Law, Crime, and Defense—and by provoking strong, often adversarial responses from other parties, including a de facto cordon sanitaire strategy, where certain parties categorically refuse to support Chega’s legislative proposals regardless of the substance. This paper contributes to the broader literature by providing new insights into how RRPs reshape parliamentary behavior, offering a case study of Portugal’s late and rapid RRP emergence. The findings underscore the critical role of these parties in disrupting consensus-driven political cultures and shaping the political debate.